The Thin Line Between Service Innovation and Brand Extension - Michael Willie (Manunggal Halim Jaya, 2026)
This study investigates the strategic integration of service innovation and brand extension within the operational frameworks of medical schemes. It aims to explore how these dual strategies can enhance competitiveness, improve service quality, and strengthen brand equity in the dynamic healthcare sector. In innovation and brand extension within medical schemes, introducing Efficiency Discount Options (EDOs) represents a departure from traditional parent benefit options, offering equivalent benefits through a distinct healthcare delivery model. This unintended consequence underscores how these pricing strategies and innovative service models can reshape consumer preferences towards more cost-effective healthcare alternatives, impacting market dynamics and demographic segmentation within the healthcare sector. This research employs a qualitative approach, focusing on in-depth case studies of medical schemes that have successfully integrated service innovation and brand extension. A comprehensive literature review complements the empirical data, providing theoretical insights into innovation and brand management strategies in the healthcare context. The study reveals that integrating service innovation and brand extension creates synergies that enhance operational effectiveness and member satisfaction, reinforcing market positioning and adaptability to evolving consumer demands. EDOs within medical schemes have inadvertently skewed beneficiary demographics toward younger age groups, showcasing how pricing strategies and innovative service models influence consumer preferences for cost-effective healthcare options. These findings underscore the strategic impact of brand extension on market dynamics and demographic segmentation in the healthcare sector, highlighting evolving consumer preferences and the competitive landscape shaped by innovative pricing and service strategies. This research contributes to the academic discourse by providing actionable insights into the effective integration of service innovation and brand extension within medical schemes. It highlights practical implications for schemes looking to optimise service administration strategies and strengthen their competitive edge in the healthcare sector. The findings also underscore the importance of aligning innovation initiatives with brand management practices to foster sustained growth and enhance service quality.